2016
DOI: 10.1159/000455901
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of the Epstein-Barr Virus and p16 Status in Patients with Nasopharyngeal Carcinoma: A Single-Centre Study in Japan

Abstract: Background: The clinical significance of the Epstein-Barr virus (EBV) status and p16 expression was unknown in nasopharyngeal carcinoma (NPC). Methods: We retrospectively studied our pathology database for 13 years to determine the prevalence of EBV and p16 expression and their association with prognosis in cases of NPC. We performed immunohistochemistry for the p16 protein and in situ hybridization (ISH) for EBV-encoded small RNAs and human papillomavirus (HPV) DNA. Results: Of the 43 patients with NPC, 27 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…12 Other studies report that p16 expression of nasopharynx cancer is higher than usual or chronic inflammation of nasopharyngeal tissue. 16 In the current study, univariate and multivariate analyses revealed that the association between p16 expression with nodal status/pN and staging/ S were significantly correlated (P< 0.05). A previous study found that p16 regulates nodal spread via integrin.…”
Section: Discussionsupporting
confidence: 49%
“…12 Other studies report that p16 expression of nasopharynx cancer is higher than usual or chronic inflammation of nasopharyngeal tissue. 16 In the current study, univariate and multivariate analyses revealed that the association between p16 expression with nodal status/pN and staging/ S were significantly correlated (P< 0.05). A previous study found that p16 regulates nodal spread via integrin.…”
Section: Discussionsupporting
confidence: 49%
“…23 Data from the nonendemic countries of Asia also demonstrated that HPV/p16 expression is uncommon in patients with NPC. 24,25 There are reports from other nonendemic regions of the world demonstrating a possible association between HPV and NPC and its potential influence on carcinogenesis. 26 In addition, there are postulations regarding the biological plausibility of the vertical, perinatal transmission of oncogenic HPV to newborns that puts them at risk of developing NPC subsequently, and hence the potential role of community control of HPV infection and newborn vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al investigated 86 patients with NPC who were treated at The University of Texas MD Anderson Cancer Center in Houston between 2000 and 2014 and reported that p16 overexpression was found to be associated with improved progression‐free survival and locoregional control in patients with EBV+ NPC; they concluded that p16 expression may complement EBV status in predicting treatment outcomes for patients with NPC . Data from the nonendemic countries of Asia also demonstrated that HPV/p16 expression is uncommon in patients with NPC . There are reports from other nonendemic regions of the world demonstrating a possible association between HPV and NPC and its potential influence on carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 5 papers were further removed because of repeated data, and 35 articles with 2612 nasopharyngeal cancer patients were included. [16–50] 6 articles were English language and 29 literatures were Chinese language in the eligible studies. (Table 1, Table 2; Fig.…”
Section: Resultsmentioning
confidence: 99%